Peripheral Mitochondrial DNA Copy Number is Increased in Korean Attention-Deficit Hyperactivity Disorder Patients - Kim, Johanna Inhyang; Lee, Soo-Young; Park, Mira; Kim, Si Yeon; Kim, Jae-Won; Kim, Soon Ae; Kim, Bung-Nyun (Frontiers in Psychiatry, 2019)
The involvement of mitochondrial dysfunction in the pathophysiology of attention-deficit hyperactivity disorder (ADHD) has been suggested in several reports. Mitochondrial DNA (mtDNA) copy number, as well as methylation of the D-loop region and peroxisome-proliferator-activated receptor γ co-activator-1α (PPARGC1A), are considered biomarkers for mitochondrial dysfunction. We compared the mtDNA copy number and methylation ratio of the D-loop region and PPARGC1A between ADHD patients and controls. The present study included 70 subjects with ADHD and 70 age- and gender-matched healthy controls (HCs). The relative mtDNA copy number in peripheral blood cells was measured using quantitative polymerase chain reaction (qPCR) and the methylation ratio was measured using methylation-specific PCR (MSP) after bisulfite conversion. The relative mtDNA copy number was significantly higher in ADHD patients than in HCs (p = 0.028). The mtDNA methylation ratio of PPARGC1A was decreased in ADHD patients compared with HCs (p = 0.008). The elevated mtDNA copy number and decreased methylation ratio of PPARGC1A found in the ADHD patients suggest the possible involvement of mitochondrial dysfunction in the pathophysiology of ADHD. Further large cohort studies investigating the correlation between clinical markers and biomarkers of mitochondrial dysfunction are warranted.